Da’wah Television From The Perspective Of Islamic Media: A Theoretical Framework Of Ownership, Content, Management, Product, And Goal - Mohammad Rofiq; Samsuriyanto Samsuriyanto (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to formulate a comprehensive theoretical framework for da’wah television by integrating the dimensions of ownership, management, content, product, and goal. This synthesis is designed to provide a systematic academic standard for validating da’wah television claims and bridging the gap between operational management practices and the mission of socio-religious transformation. The research employs a constructivist-interpretive paradigm within a qualitative research design, utilizing a library research approach and a systematic literature review strategy. Data were gathered from major academic databases until late 2025 to ensure the inclusion of the most recent academic discussions. The data were analyzed using Qualitative Content Analysis, adapting the interactive analysis model by Miles, Huberman, & Saldaña (2014) to bridge Islamic normative ideals with media industry realities. The results obtained indicate that a robust da’wah television framework requires a circular integration where ownership influences management, which then dictates the quality of content and product, ultimately leading to the fulfillment of the goal. This cyclical flow ensures that the final media product serves as a tool for social change rather than a mere commodity, while the goal fulfillment feeds back into ownership values. The study contributes significant conceptual enrichment by providing a rigorous analytical vocabulary for Islamic media studies and explicitly mapping the tension points between religious idealism (e.g., peace journalism) and market realities (e.g., sensational conflict journalism). Although limited by the absence of primary empirical data, this theoretical framework establishes a vital foundation for future empirical validation in the modern broadcasting landscape.